Characterization of mangrove composition and anthropogenic marine debris accumulation in mangrove ecosystems of Mactan Island, Philippines (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Cortes ST, Retubado ZAZ, Colita LB, Caballero JE, Lorca AS, Rosales RC. 2024. Characterization of mangrove composition and study of anthropogenic marine debris accumulation in Mactan Island, The Philippines mangrove ecosystems. Biodiversitas 25: 3521-3530. Mangrove forests are recognized for their economic and socio-ecological importance. However, their unique morphological structures lead them to become efficient traps of waste sourced from various anthropogenic activities. The continuous accumulation of these Anthropogenic Marine Debris (AMD) could cover the forest floors, resulting in the oppression of their pneumatophores and knee roots. In the long run, this phenomenon could lead to tree death. In this regard, the study assessed the mangrove forest composition and AMD occurrence in the highly urbanized Island of Mactan as a basis for planning its conservation. Fifteen (15) quadrats in each sampling station measuring 10×10 m were established in two sites, Punta Engaño (S1) and Catarman (S2). In two sampling sites, five quadrats were established in each zone (i.e., seaward, midward, and landward). The study recorded 17 mangrove species in two sampling sites, of which all 17 species are present in S1 and four in S2. Of the 17 species, 16 are valid mangrove species belonging to seven (7) families and ten (10) genera. The presence of Pemphis acidula J.R.Forst. & G.Forst. in S1 is a significant finding of the study, as it is categorized as one of the endangered species in the Philippines. This study also confirmed the occurrence of AMD in the forest floors of the mangrove areas. A total of 5192 debris items were identified, and they weighed 213.61 kgs for both sites, covering 3,000 m2 of the island. The majority of this debris is made of single-use plastics used for packaging. These findings underscore the urgent need for local government action focused on effective waste management policies and strategies, information education campaigns, and community extension projects for the long-term survival of the mangrove forests.
Keywords: Coastal, mangrove, marine litter, Philippines, plastic contamination